Work Life Balance in Indian IT & BPO Industry - Vadehra, Pallvi; Chitkara, S. C (Journal of Commerce and Trade, 2012)
Work–Life Balance (WLB) is a broad concept including proper prioritizing between “works” on the one hand and “life” on the other. Related, though broader terms, include a “lifestyle balance” and “life balance”. The purpose of this paper is to study the styles that have been used for balancing work and family by the professionals working in Indian IT and BPO sectors and the kind of support they are getting from their organizations. Professionals may face many problems in balancing their work and life due to many demands of their careers and also fast paced life and stress in today’s competitive world.